Removal of Pyrethrin from Aqueous Effluents by Adsorptive Micellar Flocculation - Pardon K. Kuipa; Olga Kuipa (Journal of Chemistry)
The equilibrium adsorption of pyrethrin onto aggregates formed by the flocculation of micelles of the surfactant sodium dodecyl sulphate (SDS) with aluminium sulphate is reported. The experimental results were analysed using different adsorption isotherms (Langmuir, Freundlich, Redlich-Peterson, Sips, Radke-Prausnitz, Temkin, linear equilibrium, and the Dubin-Radushkevich isotherms). The Freundlich and linear equilibrium isotherms best describe the adsorption of pyrethrin onto SDS micellar flocs, with the Freundlich adsorption constant, KF, and the mass distribution coefficient, KD, of 64.266 ((mg/g)(L/mg)1/n) and 119.65 L/g, respectively. Applicability of the Freundlich adsorption model suggests that heterogeneous surface adsorption affects the adsorption. The mean free energy value estimated using the Dubinin-Radushkevich isotherm was 0.136 kJ/mol indicating that physisorption may be predominant in the adsorption process.